Monsters, Inc. ([s.l. s.n.], 2002)
Monster generate their city's power by scaring children, but they're terribly affraid themselves of being contaminated by children, so when one enters Monstropolis, top scaner fully find his world disrupted.
VCD
Keywords: Picture puzzles--Juvenile fiction; Literary recreations--Juvenile fictions; Animation Feature